POLITIK HUKUM PEMERINTAHAN DESA - Wardana, Dodi Jaya (Jurnal Justiciabelen, 2021)
The State recognizes and respects regional government units that are special or special in nature which are regulated by law. Second, the State recognizes indigenous and tribal peoples' units along with their traditional rights insofar as they are alive and in accordance with the development of society and the principles of the Unitary State of the Republic of Indonesia, which are regulated in law. Politics of village government law, it cannot be separated from 3 (three) main bases, namely philosophical, sociological and juridical basis. The politics of regulatory law above are the base for legal politics for regulations that are below, so that there should not be any universal inconsistencies. In addition, horizontally the legal politics of legislation must also be consistent.